Removing own-limb visual input using mixed reality (MR) produces a “telescoping” illusion in healthy individuals - Thøgersen, Mikkel; Flor, Herta (Behavioural brain research, 2018)
The purpose of the present study was to assess changes in body perception when visual feedback was removed from the hand and arm with the purpose of resembling the visual deprivation arising from amputation. The illusion was created by removing the visual feedback from the participants’ own left forearm using a mixed reality (MR) and green screen environment. Thirty healthy persons (15 female) participated in the study. Each subject experienced two MR conditions, one with and one without visual feedback from the left hand, and a baseline condition with normal vision of the limb (no MR). Body perception was assessed using proprioceptive drift, questionnaires on body perception, and thermal sensitivity measures (cold, warm, heat pain and cold pain detection thresholds). The proprioceptive drift showed a significant shift of the tip of the index finger (p<0.001) towards the elbow in the illusion condition (mean drift: −3.71cm). Self-report showed a significant decrease in ownership (p<0.001), shift in perceptual distortions, (e.g. “It feels as if my lower arm has become shorter”) (p=0.025), and changes in sensations of the hand (tingling, tickling) (p=0.025). A significant decrease was also observed in cold detection threshold (p<0.001), i.e. the detection threshold was cooler than for the control conditions. The proprioceptive drift together with the self-reported questionnaire showed that the participants felt a proximal retraction of their limb, resembling the telescoping experienced by phantom limb patients. The study highlights the influence of missing visual feedback and its possible contribution to phantom limb phenomena.
Gesehen am 08.12.2020